EXTERNAL CONDITION TO ECO-BEHAVIOURS IN MELAKA GREEN CITY - Abu Bakar, Aisyah; Mustapa, Siti Indati; Mohammad, Norsyahida (PLANNING MALAYSIA, 2020)
External Condition [EC] to eco-behaviours relates to the macro context of a person representing the person’s façade towards his context. EC manifests in the perception and attitude towards surrounding circumstances such as the accessibility to conducive natural surroundings, encouragement to pro environmental behaviours, convenience to be environmentally responsible and favourable law enforcement. Issue: 10 years has passed since the Green City Action Plan [MGCAP] and Sustainable Urban Development Framework [SUDF] were introduced. The Melaka EC to eco-behaviours needs to be assessed to determine the impact of the MGCAP and SUDF to EC of eco-behaviours. Purpose: This paper aims to compare the EC of Melaka residents to residents of other states in Malaysia. Approach: One-Way MANOVA was generated to determine the mean distribution of 10 EC items, across Malaysia States. Findings: There were significant differences within subjects of the 10 EC items between-subjects of Malaysia States. The Post-Hoc Test indicated almost all of the means of EC items for Melaka were higher than other states. The MGCAP and the SUDF shows a positive impact on the EC to a sustainable community.